Modeling development of breast cancer: from tumor microenvironment to preclinical applications - Tang, Ruizhi; Liu, Xi-Qiu (Frontiers in Pharmacology, 2024)
Breast cancer is a complex disease and its progression is related not only to tumor cells but also to its microenvironment, which can not be sufficiently reflected by the traditional monolayer cell culture manner. The novel human cancer models comprising tumor microenvironment (TME), such as tumor organoids and organs-on-a-chip, has been established in recent years to help elucidate the underlying mechanisms of tumorigenesis and promote the development of cancer therapies. In this review, we first discuss the current state of breast cancer and their treatment strategies, and elucidates the complex properties of TME of breast cancer in vivo. The culture models used in breast cancer research are then summarized with insights into recent development. Finally, we also conclude by discussing the current limitations and future directions of culture models in breast cancer research for providing a preclinical reference for the precise treatment of cancer patients.